2017
DOI: 10.12681/jhvms.15577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic acids on the gut ecosystem and on the performance of broiler chickens

Abstract: Organic acids are studied as candidate alternatives to antibiotic growth promoters. Their action is related to the pH reduction of the intestinal digesta, affecting the gut ecosystem in numerous ways. Intestinal microbiota can be altered as a result of the remarkable antibacterial activity of organic acids and the growth enhancement of non-pathogenic beneficial microorganisms, due to exclusive competition. Antibacterial activity has been widely reported for many poultry pathogens, such as Salmonella spp., Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…As multi resistant bacteria rise as a problem and are a major health hazard, new reduction measurements are developed to reduce specific bacterial fractions of the intestinal microbiota in animals. Nutritional intervention steps have shown promising results to shift the microbiota towards a more desirable direction [29,30,31,32,33,34]. This may create stress for the suppressed bacteria, causing a change in their metabolic activity, including the transfer of genetic material [35,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…As multi resistant bacteria rise as a problem and are a major health hazard, new reduction measurements are developed to reduce specific bacterial fractions of the intestinal microbiota in animals. Nutritional intervention steps have shown promising results to shift the microbiota towards a more desirable direction [29,30,31,32,33,34]. This may create stress for the suppressed bacteria, causing a change in their metabolic activity, including the transfer of genetic material [35,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [23] also found that SCFAs can affect the secretion of the epithelial repair cytokine interleukin-18. And they found that the decreased of Bacteroides and Clostridium sub-cluster XIVab leading to the decrease of organic acid, which reduces the trophic effect of organic acid to epithelial cells and the inhibitory effect on pathogenic bacteria [39]. Agus et al [40] found that the reduced of certain intestinal flora inhibited the conversion of tryptophan to indole and its derivatives, and AhR as a receptor of indole and its derivatives, its activation will reduced, thereby inhibiting the intestinal TJP and AhR-Nrf2 pathway, leading to the reduced of intestinal barrier integrity and increased oxidative stress [41].…”
Section: The Role Of Gut Microflora In Ucmentioning
confidence: 99%